Implikasi Foreign Direct Investment Jepang melalui Toyota terhadap Perekonomian Indonesia Periode 2016-2022 - Aldella Alfia Hardzi; Sugito Sugito (Mahesa Research Center, 2023)
This article focuses on cooperation between Japan and Indonesia through the development of a Toyota subsidiary in Indonesia as an instrument for Japanese Foreign Direct Investment. Japan is a country that has quite an important role in the international world because of its development in the economic sector, where currently Japan can dominate the international market through advances in automotive technology. The rapid development of the automotive industry has encouraged Japan to invest in Indonesia. This article aims to find out what the results of Indonesia-Japan FDI cooperation are through the development of Toyota in Indonesia in 2016-2022. In order to approach this problem, references to the theories of liberalism, bilateral cooperation and Foreign Direct Investment are used. Data was collected through secondary data as a data source, as well as using desk review and analyzed qualitatively. This study concludes that Japanese FDI through the Toyota company has enabled Indonesia to improve its economy through a high increase in the value of exports to several countries, expanding employment opportunities, as well as providing a positive impact on improving environmentally friendly technology.